Cyclic Digital Transmission Communication Software Design and Realization - Gao, Teng; Zou, Ji-Yan; Song, Jin-Yan; Ding, Jin-Hua; Wang, De-Quan; Si, Zhen-Yuan (Recent Advances in Electrical & Electronic Engineering, 2016)
The devices in the intelligent substation are required to transmit and process information in Smart Grids. On account of the modular design technology, serial port communication becomes the main technique used to connect intelligent modules as its high reliability, flexibility, and ease-of-use features, which is also used in the communication of the data collection board and the conversion board of the three-phase circuit breaker. Cyclic Digital Transmission (CDT) protocol, which is issued by the Ministry of Energy of China, is widely used in the communication of the power system in China. The framework of CDT protocol is composed of the function, the information word, the transfer rules and the frame structure. The CDT protocol that adopts STM32 as the CPU is developed in this paper, so as to achieve highly automated grid scheduling and reliable and stable communication. Some functions and technologies of STM32 such as Timer, USART, DMA, etc., are described in detail. The test results indicate that the serial port reliable communication based on CDT protocol can be realized, which also shows that the data collection board can communicate with the dispatch center via the protocol conversion board.
Keywords: serial port